Religion and Democracy: Perspective of Abdurrahman Wahid - Elly Warnisyah Harahap; Syahrin Harahap; Amroeni Drajat (Budapest International Research and Critics University, 2020)
This paper describes the thoughts of Abdurrahman Wahid (Gus Dur) about religion and democracy. Abducting Abdurrahman's thoughts about religion and democracy today is not only relevant, but important, especially in the midst of various radicalism issues that are currently being discussed today. The issue of radicalism which is generally directed at Muslims is suspected because of the desire of a group of Muslims to make Islam appear in its formal form in this country, in other words they want to make Indonesia an Islamic state. This desire which was opposed by Abdurrahman by considering the plurality of the nation, especially according to Abdurrahman, there is no standard provision of the state in Islam. By using library data, it is concluded that specifically in seeing the relationship between Islam and democracy there are three kinds of responses, namely integrative, facultative, and confrontational. In addition, Abdurrahman firmly said that Islam does not need to be present in a formal form in this country, just enough substance that is when Islamic values are realized in democracy, because the teachings of democracy do exist in Islam.